Respuesta del cultivo de arveja (Pisum sativum L.) a la aplicación complementaria de tres fertilizantes foliares a tres dosis. San Gabriel. Carchi - Flores Flores, Mauricio Alejandro (2010)
The farmers with the aim of increasing in the performances, quality of their products have considered the bio-stimulant use, like an one belonging to the alternatives for the better and giving a total spin to the national production for which this investigation presents like objectives: Determining which one of the fertilizers allows foliar improving the production of the cultivation of green pea in San Gabriel, Carchi; Determining which one of the doses of the fertilizers allows diligent foliar improving the production of green pea; Determining which one of the interactions between fertilizers foliar and dose of fertilizer applied in the essay; Accomplishing the production costs of the treatments of the essay.